Product Recall and Customer Relationship Recovery: Developing an Integrative Framework through a TCCM-Based Systematic Literature Review - Ucu Supriatna; Mohamad Ichsana Nur; Evi Sofiati (Business and Applied Management Journal, 2026)
Product recalls threaten customer trust, satisfaction, loyalty, and brand equity, creating a need to understand how firms can recover relationships after product failures. This study aims to map the literature on product recall and customer relationship recovery, identify research gaps, and develop an integrative conceptual framework. Drawing on crisis management, service recovery, justice, trust repair, organizational capability, and digital communication perspectives, the study conducts a systematic literature review of 40 Scopus-indexed Q1–Q2 articles published between 2016 and 2026. Article selection follows PRISMA 2020, while synthesis applies the theory–context–characteristics–methodology framework. The findings show that crisis management, remedy selection, consumer relational responses, and quantitative archival methods dominate research. In contrast, integrative frameworks, operational capabilities, competitor responses, digital analytics, and mixed methods remain limited. The study proposes a sequential framework linking risk detection, recall decisions, communication, remedies, consumer participation, and relationship recovery, thereby extending theoretical integration and managerial guidance for post-recall recovery.